Using situational approach to forming control algorithms for batch vacuum pans - Прокопенко, Юрій Володимирович; Ладанюк, Анатолій Петрович (Eastern-European Journal of Enterprise Technologies, 2015)
Forming new criteria for sugar production processes poses the problem of developing and introducing innovative control methods and systems. Using situational control methods is promising. In the paper, the problem of the batch vacuum pan control using the situational approach, taking into account new process criteria: temperature, level of syrup in the vacuum pan, operation modes was considered. Based on the predication graph constructed and linguistic interpretation of the system description by the expert planer, a system of commands for the situational control of the batch vacuum pan was developed. Using the developed system of commands, the situational control algorithm for the batch vacuum pan was built, shortcomings and future research directions were discussed. The results allow to conclude about the prospects of further works on introducing the situational control for developing hierarchical multi-level control systems for manufacturing facilities, take into account such important factor as operator intervention in the production process.